The Effect Of The Use Of Birth Ball On Intensity Of Labor Pain I Active Phase In Primigravidal Mothers In Pmb Bekasi City In 2022 - Rica Sahara; Febry Mutiariami Dahlan; Cholisah Suralaga (Science Midwifery, 2022)
Childbirth is a natural process.Discomfort, fear and pain is a problem for mothers in labor. Pain in the first stage of the active phase of labor is severe pain with a longer time, therefore it is necessary to pay attention to handling to overcome pain in the first stage of labor. This study aims to determine the effect of the use of birth balls on the intensity of labor pain in the active phase of the first stage of primigravida mothers in PMB Bekasi City 2022. This study uses a quasi-experimental approach. The sample in this study was 30 respondents, namely 15 mothers in the control group and 15 mothers in the intervention group. The instrument used is an observation sheet on the implementation of the use of a birth ball. The analysis used is univariate analysis and bivariate analysis using Independent T test and Paired T - Test. HThe results of the univariate analysis showed that in the intervention group the average level of pain before the birth ball was done the average pain level was 7.46 and after it was done it was 4.46. The mean level of pain in the control group on examination 1 was 7.06 and on examination 2 was 6.80. The results of the bivariate analysis showed that there was an effect of using a birth ball on the pain of labor in the first stage of the active phase in primigravida mothers with a p value of 0.000. There is no effect of not using a birth ball on the pain of labor in the first stage of the active phase of primigravid mothers with a p value of 3.64. There was a difference in the decrease in pain level in the first stage of the active phase in primigravida mothers in the intervention group and the control group with a p value of 0.000. The results of this study can be concluded that the use of birth balls is effectively used to reduce labor pain in the first stage of the active phase of primigravida mothers